KEPEDULIAN SISWA MADRASAH ALIYAH TERHADAP PRODUK PANGAN HALAL DI KOTA SURAKARTA - Umi Muzayanah; Setyo Boedi Oetomo; Zakiyah Zakiyah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2019)
Indonesia, as the country with the world’s largest Muslim population, has issued a regulation on halal product assurance (UU JPH) Act No. 33/2014. Furthermore, the consumers’ care on the halal food is another significant element in the implementation of this regulation. This study concerns on how the students of Islamic Senior High School (MA) in Surakarta care on the halal food products. This is a quantitative study in which data were collected using questioners. There are 430 selected students participated in this study. Data was analyzed using descriptive analysis by counting the mean score and classified into four categories namely; do not care, less care, quite care, and care. Findings of this research showed that most students are “quite care” for halal product, but they mostly did not ask to the merchants whether the product they bought to have “haram” ingredients or not. Moreover, the majority of students sometimes checked the halal label on the product, while others did not check them at all. Overall, the students’ care level toward halal product is categorized as at the “quite care”. This result indicated that it needs more concern from the related stakeholders on how the students can be more attentive toward halal food products.